Praktyczny wymiar instytucji czasowego odebrania zwierzęcia właścicielowi lub opiekunowi - Sługocka, Martyna (Wydawnictwo Uniwersytetu Wrocławskiego, 2017)
Animal rights issues in particular cruelty to animals became an object of interest to the doctrine representatives as well as the whole society. This article shows how the police and representatives of social organizations, whose statutory purpose is to protect animals, can help victims of violence. The author discusses the administrative procedure according to which the public administration bodies self-government administration should operate. At the same time, the author draws attention to the problems brought about by the application of the discussed legal regulations in practice.
Keywords: ochrona zwierząt; okrucieństwo wobec zwierząt; administracyjne procedury; policja